Palestinian law to protect family and prevent violence: challenges with public opinion - Fayez Mahamid; Muayad Hattab; Denise Berte (BMC, 2023)
Abstract The Palestinian Family Protection Law was submitted for ratification in November 2020 after much collaboration between advocates, attorneys and governmental officials, as well as community and international organizations. The draft bill addresses a myriad of social issues affecting vulnerable populations in the West Bank of Palestine, including: the legal age for marriage; gender inequality in inheritance; divorce; gender-based violence; and domestic violence. However, immediate feedback from local religious scholars, with increasing pressure from the general Palestinian population, was deeply divided, with negative perceptions relating to the perceived 'foreign' nature of the regulations and criticism that the law was not in accordance with Palestinian culture and Islamic Law. This criticism led to two years of inactivity regarding the bill. The current study sought to evaluate the attitudes, behavior and beliefs regarding the underlying human rights issues and assumptions concerning gender, marriage, and domestic violence that could be found in the codices of the proposed legislation as well as among the general population of Palestine. The data demonstrates that the population sampled viewed the underlying premise of the Family Protection Bill negatively. Individuals with a graduate degree or above tended to view the bill with less negativity, whilst females viewed the bill more positively than males. The results of this study illustrate that, with regard to legislation that relates to family life in Palestine, there is a wide gap between the points of view held by human rights advocates and NGO's and those held by the general population. To further the agenda of family protection community education relating to social issues, the fundamentals of Sharia law and national sovereignty may be needed so as to clarify the core Islamic beliefs in relation to human rights and oppression, as well as to increase Palestinian ownership of the family protection agenda.